Gas Geochemistry at Grande Comore and Mayotte Volcanic Islands (Comoros Archipelago), Indian Ocean. (17th August 2021) - Liuzzo, Marco; Di Muro, Andrea; Rizzo, Andrea Luca; Caracausi, Antonio; Grassa, Fausto; Fournier, Nicolas; Shafik, Bafakih; Boudoire, Guillaume; Coltorti, Massimo; Moreira, Manuel; Italiano, Francesco
Abstract: The Comoros archipelago is an active geodynamic region of intra‐plate volcanism within which the youngest and oldest islands (Grande Comore and Mayotte respectively) are characterized by recent volcanic activity. The frequent eruptions of the large shield volcano Karthala on Grande Comore (last eruption 2007), and the recent birth of a large submarine volcano since 2018 at the submarine base of Mayotte are associated with permanent fumarolic emissions, bubbling gas seeps, and soil gas emissions, which are studied in detail here for the first time. CO2 fluxes and chemical and isotopic gas compositions acquired during two surveys in 2017 and 2020 are integrated with older data sets collected between 2005 and 2016, permitting the identification of a possible influence of the recent volcanic and magmatic activity at Mayotte. At Karthala, high gas fluxes with high temperature, and a marked magmatic signature are concentrated close to the summit crater area, while only weaker emissions with a stronger biogenic signature are found on the volcano flanks. At Mayotte, lower temperature and higher CH4 content are recorded in two main seep areas of CO2 ‐rich fluid bubbling, while soil emissions on land record a higher proportion of magmatic fluids compared to Karthala. Our preliminary results reveal two quite separate gas emission patterns for each island that are distinct in composition and isotopic signatures, and well correlated with the present state of volcanic activity. This work may potentially provide support for local observation infrastructures and contribute to the improvement in volcanic and environmental monitoring. Key Points: Map of the spatial distribution of ground CO2 emissions and its isotopic characteristics in both islands Grande Comore and Mayotte Geochemical characterization of fumarolic and hydrothermal gases in terms of both primary component species and isotopic characteristics Correlation between the variability of geochemical tracers and the new submarine volcano off Mayotte and its implications for the risk to the island's inhabitants